PERAN PEMERINTAH DAERAHKOTAPEKANBARU DALAM PENYEDIAAN RUANG KHUSUS MENYUSUI DI INSTANSI PEMERINTAHAN BERDASARKANPERATURAN WALIKOTA PEKANBARU NOMOR48TAHUN2015 TENTANG PEMBERIAN - Rahmawita Asari; Emilda Firdaus; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The issuance of the mayor’s regulation of Pekanabaru Number 48 of 2015 conceringthe provision of exclusive breast milk, article 3 paragraph 1 which states the support forexclusive breastfeeding must be carried out by families, communities, state/private-ownedenterprises, city governments and the support as referred to in paragraph 1 covers theprovision of breastfeeding times and places to breastfeed (ASI corner). The formulation ofthe problem in this thesis, namely: First, the role of the local government of the city of newweek in an effort to provide a special room for breastfeeding in government agencies.Second, the inhibiting factor in the effort to provide a special room for breastfeeding ingovernment agencies. Third, the efforts that must be made by the Pekanbaru city governmentare to maximize the provision of special breastfeeding rooms in government agencies.This type of research is a sociological legal research, because it is based on fieldresearch, namely by collecting data from interviews questionnaires, and literature studiesthat are related to the problems to be studied, assisted by primary, second and tertiary data.The research was conducted at the Pekanbaru City Health Office, the Pekanbaru Mayor’sOffice, the Pekanbaru Public Service Mall, the Pekanbaru City Women and ChildrenEmpowerment Service, Sail District,Binawidya District , and the Pekanbaru City RegionalPeople’s Representative Council of Pekanbaru city. While the population and sample are allparties related to the problem under study, namely all regional apparatus organizations inthe city of Pekanbaru and female employees who work in the office or government agency ofthe city of Pekanbaru. This study uses qualitative data analysis and produces descriptivedata.From the results of the study if can be conclude that. First, the role of the PekanbaruCity government in providing a special breastfeeding room in government agencies has notrun optimally. Second, the inhibiting factors from the implementation of the provision ofspecial breastfeeding room in government agencies are regulatory factors, budget factor,lack of coordination factors, human resources factors,lack of data collection, lack ofsocialization, education and information and supervision factors. Third, the efforts that havebeen made to overcome the inhibiting factors are, establishing standard operatingprocedures, and conducting counselingKeywords: Role-exclucive mother’s milk room-special room for breastfeeding